MicroRNA-206 inhibits stemness and metastasis of breast cancer by targeting MKL1/IL11 pathway - Samaeekia, Ravand (Clin Cancer Res, 2016)
PURPOSE: Effective targeting of cancer stem cells is necessary and important for eradicating cancer and reducing metastasis-related mortality. Understanding of cancer stemness-related signaling pathways at the molecular level will help control cancer and stop metastasis in the clinic. EXPERIMENTAL DESIGN: By analyzing microRNA profiles and functions in cancer development, we aimed to identify regulators of breast tumor stemness and metastasis in human xenograft models in vivo and examined their effects on self-renewal and invasion of breast cancer cells in vitro. To discover the direct targets and essential signaling pathways responsible for microRNA functions in breast cancer progression, we performed microarray analysis and target gene prediction in combination with functional studies on candidate genes (overexpression rescues and pheno-copying knockdowns). RESULTS: In this study, we report that hsa-miR-206 suppresses breast tumor stemness and metastasis by inhibiting both self-renewal and invasion. We identified that among the candidate targets, twinfilin (TWF1) rescues the miR-206 phenotype in invasion by enhancing the actin cytoskeleton dynamics and the activity of the mesenchymal lineage transcription factors, megakaryoblastic leukemia (translocation) 1 (MKL1) and serum response factor (SRF). MKL1 and SRF were further demonstrated to promote the expression of interleukin-11 (IL-11), which is essential for miR-206’s function in inhibiting both invasion and stemness of breast cancer. CONCLUSION: The identification of the miR-206/TWF1/MKL1-SRF/IL-11 signaling pathway sheds lights on the understanding of breast cancer initiation and progression, unveils new therapeutic targets, and facilitates innovative drug development to control cancer and block metastasis.